Comparing steamed and wine-stewed Rehmanniae Radix in terms of Yin-nourishing effects via metabolomics and microbiome analysis. (15th July 2023) - Zhang, Xiao-Ya; Xu, Jin-Di; Wang, Yao; Wu, Cheng-Ying; Zhou, Jing; Shen, Hong; Zou, Ye-Ting; Zhu, Jin-Hao; Zhou, Shan-Shan; Li, Song-Lin; Xu, Jun; Long, Fang
Abstract: Ethnopharmacological relevance: Rehmanniae Radix Praeparata (RRP), the processed root of Rehmannia glutinosa, has been widely used to treat Yin deficiency syndrome in traditional Chinese medicine. RRP is available in two forms: processed by steaming with water (SRR) or processed by stewing with yellow rice wine (WRR). Previous work has documented chemical differences in the secondary metabolomes and glycomes of SRR and WRR. Aim of the study: This study aimed to compare SRR and WRR in terms of Yin-nourishing effects via metabolomics and microbiome analysis. Materials and methods: ICR mice were orally administered with thyroxine for 14 d to induce Yin deficiency. Changes in biochemical indices and histopathology were detected. Serum metabolomics analysis and microbial 16S rRNA sequencing were performed to compare the therapeutic effects and mechanisms between SRR and WRR in treating thyroxine-induced Yin deficiency. Results: Both SRR and WRR decreased serum T3, T4 and MDA levels, and increased SOD activity. SRR more effectively decreased serum Cr, and ameliorated kidney injury, while WRR showed better regulation on ratio of cAMP/cGMP and serum TSH, and relieved thyroid injury. Both SRR and WRR regulated tyrosine, glycerophospholipid, and linoleic acid metabolism and the citric acid cycle. Additionally, SRR regulated fatty acid metabolism, while WRR influenced alanine, aspartate and glutamate metabolism, and bile acid biosynthesis. SRR significantly enriched the genera Staphylococcus and Bifidobacterium in the gut microbiome, while WRR significantly enriched the genera Akkermansia, Bacteroides and Parabacteroides, and decreased the abundance of Lactobacillus . Conclusions: SRR displayed better protective effects on kidney, while WRR showed stronger effects on thyroid in thyroxine-induced Yin deficient mice. These differences might be due to different regulating effects of SRR and WRR on the metabolome and gut microbiota. Graphical abstract: Image 1 Highlights: Yin-nourishing effects of SRR and WRR were compared in vivo. High-dose thyroxine was used to induce Yin deficiency syndrome state in mice. SRR displayed better protection on kidney, while WRR showed better on thyroid. SRR and WRR showed different regulation on metabolome and gut microbiota.